La tecnología como herramienta educativa: Insumos para una posible reforma curricular en la carrera de Enseñanza de la Matemática en la Universidad Nacional - Morales López, Yuri (2009)
The aim of this paper is to formulate a proposal for the incorporation of Technology as an educational tool in the initial training of teachers of Mathematics. For this, we analyze the current situation regarding the use of Technology in Higher Education and it’s exemplified through for the Mathematics Teaching Program of the Universidad Nacional in Costa Rica. Also, it establishes some general and specific actions for Curriculum Reform in the area of Technology within this program.